The dynamics of corporate co-evolution a case study of port development in China - Child, John (Edward Elgar Pub, 2013)
pt. I. Introduction, perspective and method -- pt. II. Environment, evolution and managerial initiative -- pt. III. Co-evolution : theory and practice
Keywords: Electronic books; Corporations -- Growth; Harbors -- China